1998
DOI: 10.1007/s004240050730
|View full text |Cite
|
Sign up to set email alerts
|

Energy state and myosin heavy chain isoforms in single fibres of normal and transforming rabbit muscles

Abstract: Energy-rich phosphates, [ATP]/[ADPfree] ratios, and the myosin heavy chain (MHC) complement were determined in single fibres from normal rabbit muscles, and in fibres isolated from tibialis anterior muscle undergoing fast-to-slow conversion by chronic low-frequency stimulation (CLFS). In normal muscles, energy-rich phosphate contents and [ATP]/[ADPfree] ratios could thus be assigned to different MHC-based fibre types. Phosphocreatine (PCr) contents and [ATP]/[ADPfree] ratios differed markedly between fast- and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
45
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 28 publications
3
45
0
Order By: Relevance
“…Furthermore, as demonstrated Table 2 Results of chronic low-frequency stimulation (CLFS) inthe sham and CLFS groups. (ATWC Work capacity at the anaerobic threshold, ATV _O 2 oxygen uptake at the anaerobic threshold, BPD diastolic blood pressure, BPS systolic blood pressure, HR heart rate, Peak-RER peak respiratory exchange ratio) in rabbit muscle by single fiber electrophoresis, CLFS results in pronounced increases in fibers displaying the co-existence of MHCIIa and MHCI during the type IIA to type I fiber transformation (Staron et al 1987;Conjard et al 1998;Peuker et al 1998). …”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, as demonstrated Table 2 Results of chronic low-frequency stimulation (CLFS) inthe sham and CLFS groups. (ATWC Work capacity at the anaerobic threshold, ATV _O 2 oxygen uptake at the anaerobic threshold, BPD diastolic blood pressure, BPS systolic blood pressure, HR heart rate, Peak-RER peak respiratory exchange ratio) in rabbit muscle by single fiber electrophoresis, CLFS results in pronounced increases in fibers displaying the co-existence of MHCIIa and MHCI during the type IIA to type I fiber transformation (Staron et al 1987;Conjard et al 1998;Peuker et al 1998). …”
Section: Discussionmentioning
confidence: 98%
“…Also in human muscle, mismatch between MyHC mRNA and protein or MyHC-ATPase reactivity could not be attributed to variations in myosin composition along the length of the fiber because the staining of fibers did not change after extended analysis of serial sections (Andersen and Schiaffino 1997). Single-fiber analysis has shown that the MyHC expression can vary along the length of the fiber, but over distances in the millimeter range, much larger than the distances between the serial sections presented here (Peuker and Pette 1997;Conjard et al 1998). …”
Section: Discussionmentioning
confidence: 99%
“…Upon this induced transformation, regardless of the type of protocol applied, more mismatching between mRNA and protein expression is observed (Andersen and Schiaffino 1997;Conjard et al 1998;Andersen et al 1999a;Stevens et al 1999). Clearly, analyzing muscle fibers (pure and hybrid) at the mRNA and protein level is important for understanding the steady-state situation and the transformation process.…”
Section: Discussionmentioning
confidence: 99%
“…Another study (Conjard et al 1998) analyzed single fibers from rabbit rectus femoris, extensor digitorum longus, tibialis anterior, and soleus muscle. mRNA MyHC isoform patterns were consistent with MHC protein profiles, including hybrid fibers, in the majority of fibers from normal, untransforming muscle (Conjard et al 1998). In rat, single fibers from the soleus muscle were analyzed; in Table 1D) stained with the indicated mRNA probes (left panels) or with the indicated antibodies (right panels).…”
Section: Discussionmentioning
confidence: 99%